Growth, production and water consumption of coriander grown under different recirculation intervals and nutrient solution depths in hydroponic channels * - Silva, Mairton Gomes da; Soares, Tales Miler; Gheyi, Hans Raj; Costa, Islan Passos; Vasconcelos, Rafael Souza (Emirates Journal of Food and Agriculture, 2020)
Water is an increasingly scarce resource in arid and semiarid regions. The irregular precipitation makes hydroponics a recommended technique for these regions, since it demands less water compared to conventional cropping systems. Two experiments, one from May to June 2016 (autumn) and other from March to April 2017 (summer-autumn), were conducted in a hydroponic system in PVC tubes, using the Deep Flow Technique (DFT). A 2 x 3 x 2 factorial arrangement in split-plot was used, which consisted of two nutrient solution depths (0.02 and 0.03 m) and three recirculation intervals of the nutrient solution (0.25, 12 and 24 h), with two coriander cultivars (‘Tabocas’ and ‘Verdão’) in the sub-plots, which were cultivated in the same hydroponic channel. Plant height, shoot fresh and dry matters, water consumption, water use efficiency and visual quality of the coriander plants were evaluated. The coriander cv. ‘Verdão’ was more tolerant to climatic variations, especially when plants were grown in channels with nutrient solution depth of 0.02 m and recirculation interval of 0.25 h, presenting higher growth and production. The recirculation intervals of 12 and 24 h had a negative effect on the variables evaluated; though, this effect was more significant in the summer-autumn experiment, affecting the quality of the plants harvested, especially those of the cv. ‘Tabocas’. It may be concluded that the cultivation of the coriander in the DFT system in PVC tubes is viable, especially in sites with insecure electricity supply. * Paper extracted from the doctoral thesis of the first author presented in the Post Graduate Program in Agricultural Engineering of the Federal University of Recôncavo of Bahia, Brazil